Efficacy of the Health Beliefs Model –Based Intervention in Enhancing Workers' Adherence to Wearing Personal Protective Equipment in Diyala State Company: A Randomized Control Trial - Tuoma, Nedaa Q.; Qassim, Wissam J. (Journal of Neonatal Surgery, 2025)
Objective(s): The study aims to determine the efficacy of the Health Belief Model – intervention in enhancing workers' adherence to wearing personal protective equipment at diyala state company. Methodology: True experimental design, using randomized controlled trial approach for the period of February 1th 2024 through January 1th 2025. The sample of the study is "A probability" simple random sample and it consist of (100) worker, who are work at factories in Diyala state company. The sample is randomly selected and assigned to the study and control groups of (50) workers each for who are equally distributed from each factory. The intervention for the study group involved a health intervention lecture about occupational hazards and PPE used based on HBM. Analyzed data using SPSS, Version23 using descriptive statistics, and inferential statistics and mixed design analysis of variance (ANOVA). Results: Findings of this study depict that there were statistically significant differences among all concepts of the health belief model related to occupational hazards prevention by using PPE. Conclusion and Recommendations: This study concluded that Applying health belief model, demonstrates the importance of PPE use in prevention of occupational hazard or accident in workplace and has a positive impact on workers' behaviors. Finally, the study recommends the need to repeated future studies based on HBM on large number of workers in the industrial or manufactory in Iraqi, with the goal of enhancing workers' behavior toward PPE using